Experimental and numerical studies of laser-welded stainless steel channel sections under combined compression and major axis bending moment - Liang, Yating (2022)
This paper presents an in-depth experimental and numerical investigation into the behaviour of laser-welded stainless steel channel sections under combined compression and bending moment about the major axis. Two laser-welded austenitic stainless steel plain channel sections were considered in the experimental investigation, and for each channel section, four eccentrically loaded stub column tests were conducted under various initial loading eccentricities. The experimental results were then adopted in a numerical investigation for the validation of finite element models, by means of which parametric studies were conducted to generate further structural performance data over a wider range of cross-section sizes and initial loading eccentricities. Both the obtained experimental and numerical results were carefully analysed and then used to evaluate the accuracy of the current codified design rules for welded stainless steel channel sections under combined compression and major axis bending. The evaluation results generally revealed that the codified design rules yield excessively conservative and scattered resistance predictions, owing to the neglect of the favourable material strain hardening of stainless steel and the beneficial stress redistribution within channel sections under combined loading. An improved design approach has been proposed through extension of the deformation-based continuous strength method (CSM) to the case of laser-welded stainless steel channel sections under combined compression and major axis bending. Quantitative evaluation of the new design approach was made through comparing the predicted resistances against the experimental and numerical failure loads, with the results revealing that the new design approach yields a much higher level of design accuracy and consistency than the current codified design rules. Finally, statistical analyses have been conducted to confirm the reliability of the new design approach according to EN 1990.